Continuing Significance of the Model Minority Myth: The Second Generation - Park, Lisa Sun-Hee (Social justice, 2008)
Part of a special issue on Asian and Pacific Islander populations within the U.S. A study was conducted to examine how second-generation Asian-Americans' retelling of their families' migration narratives are influenced by the myth of the Asian-American “model minority.” Data were obtained from interviews conducted with Korean- and Chinese-American youth, which exemplify both the typical migration narrative and the tendency to reinforce the model minority trope. Findings indicated how the model minority myth not only has an ongoing role to play in perpetuating the marginal status of Asian Americans, but also one in limiting the avenues for progressive social change among the second generation. Findings suggested that the model minority myth works as a political mechanism of control that has the effect of altering one's sense of reality to justify the unequal social order. Findings are discussed in detail.